2019
DOI: 10.2478/otmcj-2019-0004
|View full text |Cite|
|
Sign up to set email alerts
|

Review of previous applications of innovative information technologies in construction health and safety

Abstract: Abstract Construction industry is one of the most hazardous industries to work in. This problem is further exacerbated by the fact that safety performance improvement is stagnating. Information technologies (ITs) are however identified as one of the most promising methods of improving the performance of construction safety. The goal of this paper was therefore to present previous research in the application of innovative ITs to the field of construction health and safety (H&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…This means from design to design through construction and operation of the construction to its liquidation [39]. The database of information created in this way allows all project participants to take into account possible errors and shortcomings, changing factors that could cause possible financial, technological and environmental problems in individual phases [40]. This can also have other economic implications [41,42].…”
Section: Building Information Modelling and Adaptive Design Of Formworkmentioning
confidence: 99%
“…This means from design to design through construction and operation of the construction to its liquidation [39]. The database of information created in this way allows all project participants to take into account possible errors and shortcomings, changing factors that could cause possible financial, technological and environmental problems in individual phases [40]. This can also have other economic implications [41,42].…”
Section: Building Information Modelling and Adaptive Design Of Formworkmentioning
confidence: 99%
“…These problems have prompted researchers (Rozenfeld et al, 2010;Zhang et al, 2015a) to explore how the JHA could be automated and applied to the construction industry. However, a review of previous research by Mihić et al (2019) revealed that previous research efforts present methods to identify only small sets of specific hazards (fall hazards, collision hazards, crane-related hazards, etc.) and that a universal hazard identification methodology is needed.…”
Section: Hazard Identification In the Construction Industrymentioning
confidence: 99%
“…This means from design to design through construction and operation of the construction to its liquidation [27]. The database of information created in this way allows all project participants to take into account possible errors and shortcomings, changing factors that could cause possible financial, technological and environmental problems in individual phases [28]. This can also have other economic implications [29][30].…”
Section: Building Information Modelling and Adaptive Design Of Formworkmentioning
confidence: 99%